SISTEM PAKAR PENGENALAN BAKAT DAN MINAT ANAK DENGAN METODE FORWARD CHAINING - Siti Uzlifatul Asma; Muhyiddin Zainul Arifin; Tholib Hariono (KH. A. Wahab Hasbullah University, 2018)
Every human being has an interest, and a different talent. Interest is a strong impetus for a person to do something he wants. Talent itself is an existing ability or innate or the ability that can be trained to master the things that interest. The potential of the child should be stimulated in advance so that it can be seen as a skill, knowledge and skillfulness that becomes the provision of his life. One way to recognize the child's talents and interests requires a test to understand the temperament and personality of the child, to understand multiple intelligences and to recognize the direction of the child's interest. The test is applied to an expert system using the Forward Chaining method to help determine the type of intelligence in the child. Each type of child intelligence has several potential talents and special interests of the child. The expert system is implemented in a Visual Basic 6.0 programming language. The results of this study in obtaining an alternative decision to recognize the type of intelligence of children who show potential talents and interests of children. So that talent can be further developed. Keywords: Talent and Interests, Forward Chaining, Expert System